PARAFFIN WAX PRECIPITATION AND DEPOSITION IN CRUDE OIL: MECHANISMS, CHALLENGES, AND MITIGATION STRATEGIES (AUN INTERNATIONAL CONFERENCE, 2025)
Paraffin wax deposition in crude oil pipelines and reservoirs poses significant challenges to flow assurance, increasing operational costs and risking blockages. This review examines the mechanisms of wax precipitation and deposition, influenced by factors such as temperature gradients, pressure fluctuations, crude oil composition, and flow conditions. Key mechanisms include molecular diffusion, nucleation, crystal growth, and interactions with asphaltenes and resins. Mitigation strategies encompass thermal (insulation, hot oil circulation), mechanical (pigging, scraping), chemical (pour point depressants, dispersants), and emerging methods like microwave/ultrasonic treatments, nanotechnology, and microbial degradation. Case studies from regions like Nigeria, Malaysia, and the Gulf of Mexico highlight successful implementations. Future trends focus on AI-driven predictive modelling, eco-friendly inhibitors, real-time monitoring, and multi-disciplinary approaches. The paper underscores the need for integrated, sustainable solutions to enhance wax management in the oil and gas industry.